Motivasi Belajar Bahasa Arab Mahasantri Lulusan “Non-Pesantren” di Institut Dirosat Islamiyah Al-Amien (IDIA) Prenduan - Bidari Bidari; Nuri Safitri (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study aims to examine the motivation to learn Arabic among students who graduated from "non-pesantren" at the Al-Amien Islamic Institute (IDIA) Prenduan. The main focus of this study is to understand the factors that encourage and inhibit the motivation to learn Arabic for students who do not have a pesantren educational background. This study uses a qualitative method with a case study approach, where data is collected through interviews, observations, and documentation. The results of the study indicate that students who graduated from non-pesantren have individual strategies in fostering motivation to learn Arabic, namely: starting with buying a vocabulary book, listening to Arabic conversations around them, bringing a dictionary, asking questions often, listening to Arabic songs, consistently memorizing vocabulary, reflecting on seniors and classmates who are proficient in Arabic, reducing sleep time, understanding their subjects. Motivation to learn Arabic among students who graduated from non-pesantren is influenced by intrinsic factors such as personal interests, academic goals, and support from the social and academic environment. These findings are expected to contribute to the development of more effective learning strategies to increase motivation to learn Arabic among students with diverse educational backgrounds.